Multifaceted folding in a foldamer featuring highly cooperative folds - Ramesh, Veera V. E.; Priya, Gowri; Kotmale, Amol S.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
Herein, we report on the folding pattern observed in a synthetic peptide featuring two highly mutually dependent, yet strikingly dissimilar, closed networks of hydrogen-bonded rings that work in a cumulative fashion to stabilize the entire folded architecture of the peptide. Structural studies unequivocally suggest that disruption of any one of these mutually-dependent hydrogen-bonded networks is deleterious to the stability of the fully folded conformation of the peptide.